2015
DOI: 10.1097/qad.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported factors associated with reengagement among HIV-infected patients disengaged from care in East Africa

Abstract: Objective Engagement in care is key to successful HIV treatment in resource-limited settings; yet little is known about the magnitude and determinants of reengagement among patients out of care. We assessed patient-reported reasons for not returning to clinic, identified latent variables underlying these reasons, and examined their influence on subsequent care reengagement. Design We used data from the East Africa International Epidemiologic Databases to Evaluate AIDS to identify a cohort of patients disenga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Camlin [2016] identified a similar spectrum of factors, with poverty and transportation resources having a greater role, and fear of mistreatment by clinic staff also playing an important role. (32) Indeed, it is possible that the outreach effort was effective in part because it mitigated concerns over staff hostility or provided encouragement to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Camlin [2016] identified a similar spectrum of factors, with poverty and transportation resources having a greater role, and fear of mistreatment by clinic staff also playing an important role. (32) Indeed, it is possible that the outreach effort was effective in part because it mitigated concerns over staff hostility or provided encouragement to patients.…”
Section: Discussionmentioning
confidence: 99%
“…(20–26) The few studies assessing re-engagement in low-income countries have focused more on descriptions of factors associated with attrition, have assessed only groups such as pregnant women, or have been qualitative in nature. (2732) No studies however have quantitatively evaluated the success of specific strategies or their timing to maximize patient re-engagement in care after loss to care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also impose burden on family and community by affecting patients' job desire and productivity level [20,23,24]. Studies also found out that higher fatigue level was reported by HIV-infected patients, who were single, unemployed, and under-weight [12,20,26,27]. Similarly, the finding of the study from USA showed that having inadequate income had an association with higher fatigue intensity [28].…”
Section: Introductionmentioning
confidence: 93%
“…The prevalence of fatigue among HIV/AIDS patients and predictors vary widely across countries and regions in the country. Several studies have reported that fatigue can negatively impact the patient's activities of daily living, quality of life, sociability, job desire, productivity, level of physical activity, psychological wellbeing, health-seeking behavior, and adherence to the HAART regimen [15,16,[18][19][20][21][22]. The cause of fatigue in HIV-infected patients is probably multifactorial.…”
Section: Introductionmentioning
confidence: 99%